Neurogenic pulmonary edema after rupture of intracranial aneurysm during endovascular coiling - Bindra, Ashish (Medknow Publications, 2011)
Neurogenic pulmonary edema (NPE) is a well-known entity, occurs after acute severe insult to the central nervous system. It has been described in relation to different clinical scenario. However, NPE has rarely been mentioned after endovascular coiling of intracranial aneurysms. Here, we report the clinical course of a patient who developed NPE after aneurysmal rupture during endovascular surgery. There was significant cardiovascular instability possibly from stimulation of hypothalamus adjacent to the site of aneurysm. This case highlights the predisposition of minimally invasive procedures like endovascular coiling to life-threatening complications such as NPE.